Anti-aging fireproof cloth for building materials and preparation method of anti-aging fireproof cloth
By modifying the glass fiber cloth and homogenizing the silicone rubber slurry, the problems of fireproof cloth being easily damaged and poor anti-aging under stress are solved, and higher tensile strength and anti-aging properties are achieved.
Patent Information
- Application Number
- CN202411668638.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-03-07
AI Technical Summary
The existing fire-resistant cloth is prone to damage under stresses such as friction, shear, and tensile. Due to the addition of flame retardant components, it is easy to react with silicone oxidation, resulting in poor anti-aging properties.
The glass fiber cloth is soaked with acid treatment and carboxymethyl cellulose solution, combined with continuous heating treatment, and modified the glass fiber cloth; at the same time, methyl vinyl silicone rubber, hydroxy silicone oil, graphite-like particles, white carbon black, triethylene diamine, platinum catalyst, and vulcanizing agent are mixed and homogenized to form a silicon rubber slurry, and heat-cured after coating on both sides of the modified glass fiber cloth.
The tensile strength of the glass fiber cloth and its compatibility with silicone rubber are improved, the anti-aging performance is enhanced, the oxidation reaction between the flame retardant components and the silicone is avoided, and the flame retardant and anti-aging properties of the fire retardant cloth are significantly improved.
Smart Images

Figure BDA0005145224890000111
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of silica gel products, and particularly relates to an anti-aging fireproof cloth for building materials and a preparation method thereof. Background Art
[0002] Fireproof cloth is a special material with flame retardant properties. Its flame retardant properties and high temperature resistance can protect the safety of people and property to a certain extent. It is usually made of glass fiber, basalt fiber and other materials. It has high temperature resistance and strength and can be used in low to high temperature environments. In terms of application scenarios, fireproof cloth can be made into fireproof curtains, electrical insulation cloth, high-temperature anti-corrosion conveyor belts, etc., which are used for fire isolation in the construction industry, thermal insulation protection of building materials, and use in high temperature environments.
[0003] Silicone rubber coated fiberglass cloth is a common fireproof cloth. Its coating is easily damaged under stress such as friction, shearing and stretching. Moreover, due to the addition of flame retardant ingredients, such as antimony trioxide, it is easy to produce oxidation reaction with silicone, resulting in poor aging resistance. It is very susceptible to aging due to factors such as light and temperature. Even if amine antioxidants are added, the effect is not very obvious. Summary of the invention
[0004] The purpose of the present invention is to provide an anti-aging fireproof cloth for building materials and a preparation method thereof in order to solve the above problems.
[0005] The present invention achieves the above-mentioned purpose through the following technical solutions:
[0006] The present invention provides a method for preparing an anti-aging fireproof cloth for building materials, comprising the following steps:
[0007] The glass fiber cloth is treated with acid and then immersed in a carboxymethyl cellulose solution, and then the glass fiber cloth is continuously heated to obtain a modified glass fiber cloth;
[0008] Methyl vinyl silicone rubber, hydroxy silicone oil, graphite-like particles, white carbon black, triethylenediamine, a platinum catalyst, and a vulcanizing agent are mixed and homogenized to obtain a silicone rubber slurry, wherein the graphite-like particles are obtained by heat-treating polyimide particles and titanium dioxide particles;
[0009] Silicone rubber slurry is coated on both sides of the modified glass fiber cloth, and the surface of the fiber cloth is heated after coating until the silicone rubber is completely cured to obtain the anti-aging fireproof cloth.
[0010] As a further optimization scheme of the present invention, the acid treatment is to treat in hydrochloric acid at a temperature of 80-90° C. and a concentration of 1.5-3.5 mol / L for 15-20 min; the concentration of the carboxymethyl cellulose solution is 7.0-10.0 wt %.
[0011] As a further optimization scheme of the present invention, the continuous heating treatment is that the temperature is raised to 300-400°C and maintained for 0.5-1h in the first stage, then raised to 1200-1300°C and maintained for 0.5-1h, and then washed with ethanol and deionized water after natural cooling.
[0012] As a further optimization scheme of the present invention, the weight proportions of the components in the silicone rubber slurry are, by weight, 80-90 parts of methyl vinyl silicone rubber, 5-10 parts of hydroxy silicone oil, 10-20 parts of graphite-like particles, 6-10 parts of white carbon black, 1-3 parts of triethylenediamine, 0.01-0.05 parts of platinum catalyst, and 1-2 parts of vulcanizing agent.
[0013] As a further optimization scheme of the present invention, the preparation process of the graphitized particles is as follows:
[0014] The polyimide particles are immersed in propylene oxide with a concentration of 10-12wt%, and then dried in a nitrogen atmosphere at 200-300°C. After drying, they are mixed with titanium dioxide particles, and the mixed particles are successively subjected to carbonization and graphitization heat treatment in a nitrogen atmosphere to obtain graphitized particles.
[0015] As a further optimization scheme of the present invention, the carbonization treatment temperature is 800-1000° C. and the treatment time is 1-2 hours, and the graphitization treatment temperature is 1700-2000° C. and the treatment time is 1-2 hours.
[0016] As a further optimization scheme of the present invention, the mass ratio of the polyimide particles to the titanium dioxide particles is 3:1.
[0017] As a further optimization scheme of the present invention, the vulcanizing agent is one of dipentadiene and tert-butyl perbenzoate.
[0018] As a further optimization scheme of the present invention, the surface of the fiber cloth is heated after coating as follows: firstly, the surface of the fiber cloth is heated at 100-120°C for 2-5 minutes, then the temperature is increased to 150-180°C and the heating is continued for 5-10 minutes until the silicone rubber is completely cured.
[0019] An anti-aging fireproof cloth for building materials is prepared by the above preparation method.
[0020] The beneficial effects of the present invention are:
[0021] The present invention improves the tensile strength of the glass fiber cloth by treating the glass fiber cloth, and increases the compatibility of the glass fiber cloth with the silicone rubber slurry, so that it can be better combined with methyl vinyl silicone rubber. Polyimide particles are used instead of antimony trioxide as a flame retardant component, and titanium dioxide is used as an anti-aging component, mainly using its shielding property as a physical anti-aging means, and by high-temperature treatment of the polyimide particles and titanium dioxide particles, the flame retardancy of the polyimide is enhanced, and the titanium dioxide can be promoted to transform into a rutile type, further enhancing its stability. The present invention also uses triethylenediamine to react with free radicals in the silicone rubber slurry to further achieve an anti-aging effect. DETAILED DESCRIPTION
[0022] The present application is described in further detail below. It is necessary to point out that the following specific implementation methods are only used to further illustrate the present application and cannot be understood as limiting the scope of protection of the present application. Technicians in this field can make some non-essential improvements and adjustments to the present application based on the above application content.
[0023] 1. Materials
[0024] Unless otherwise specified, the methods used in the present invention are conventional methods known to those skilled in the art, and the reagents and other materials used are commercially available products unless otherwise specified.
[0025] The glass fiber cloth of the present invention is purchased from Fengyang Jutai Glass Fiber Co., Ltd.
[0026] The concentration of the carboxymethyl cellulose solution in the present invention is 7.0-10.0 wt %. The following examples use a 10.0 wt % carboxymethyl cellulose solution.
[0027] The acid used in the present invention is hydrochloric acid, and the concentration of the hydrochloric acid is 1.5-3.5 mol / L. 2 mol / L hydrochloric acid is used in the following examples.
[0028] The vulcanizing agent of the present invention is one of di-2-pentane and tert-butyl perbenzoate. The vulcanizing agent in the following embodiments is di-2-pentane.
[0029] The platinum catalyst and hydroxy silicone oil of the present invention were purchased from Anhui Aiyota Silicone Oil Co., Ltd., and the white carbon black was purchased from Anhui Fengyang Saijiyuan Inorganic Materials Co., Ltd.
[0030] The triethylenediamine of the present invention is purchased from Anhui Xingxin New Materials Co., Ltd.
[0031] The polyimide particles of the present invention were purchased from Anhui Keju New Materials Co., Ltd., and the titanium dioxide particles were purchased from Fengyang Huijing Nano New Materials Technology Co., Ltd.
[0032] 2. Methods
[0033] Example 1
[0034] The present embodiment provides an anti-aging fireproof cloth for building materials, and the preparation method is as follows:
[0035] (1) treating the glass fiber cloth with hydrochloric acid for 15 minutes and then soaking it in a carboxymethyl cellulose solution for 24 hours, scooping up the glass fiber cloth and subjecting it to continuous heating treatment, with the temperature in the first stage rising to 350±50°C and maintaining it for 1 hour, then rising to 1250±50°C and maintaining it for 1 hour, cooling it naturally and then washing it with ethanol and deionized water, and drying it at room temperature to obtain the modified glass fiber cloth;
[0036] (2) The polyimide particles are immersed in propylene oxide with a concentration of 12 wt%, and then dried in a nitrogen atmosphere at 200° C. After drying, they are mixed with titanium dioxide particles at a mass ratio of 3:1, and the mixed particles are put into a vacuum carbonization furnace, and carbonized and graphitized heat treatments are performed successively in a nitrogen atmosphere, wherein the carbonization treatment temperature is 800±50° C. and the treatment time is 1 h, and the graphitization treatment temperature is 1950±50° C. and the treatment time is 1 h, to obtain graphitized particles;
[0037] 80 parts of methyl vinyl silicone rubber, 5 parts of hydroxy silicone oil, 10 parts of graphite-like particles, 8 parts of white carbon black, 1 part of triethylenediamine, 0.01 parts of platinum catalyst and 1 part of vulcanizing agent were mixed, and then the mixture was homogenized by ultrasound to obtain silicone rubber slurry;
[0038] (3) Silicone rubber slurry is coated on both sides of the modified glass fiber cloth with a coating thickness of 150 μm. After coating, the surface of the fiber cloth is heated at 110±10°C for 3 min, and then the temperature is increased to 165±15°C for further heating for 5 min until the silicone rubber is completely cured to obtain an anti-aging fireproof cloth with a continuous morphology and a smooth surface.
[0039] Example 2
[0040] The present embodiment provides an anti-aging fireproof cloth for building materials, and the preparation method is as follows:
[0041] (1) treating the glass fiber cloth with hydrochloric acid for 15 minutes and then soaking it in a carboxymethyl cellulose solution for 24 hours, scooping up the glass fiber cloth and subjecting it to continuous heating treatment, with the temperature in the first stage rising to 350±50°C and maintaining it for 1 hour, then rising to 1250±50°C and maintaining it for 1 hour, cooling it naturally and then washing it with ethanol and deionized water, and drying it at room temperature to obtain the modified glass fiber cloth;
[0042] (2) The polyimide particles are immersed in propylene oxide with a concentration of 10 wt%, and then dried in a nitrogen atmosphere at 200° C. After drying, the particles are mixed with titanium dioxide particles at a mass ratio of 3:1, and the mixed particles are put into a vacuum carbonization furnace, and successively subjected to carbonization and graphitization heat treatment in a nitrogen atmosphere, wherein the carbonization treatment temperature is 900±50° C., the treatment time is 1 h, and the graphitization treatment temperature is 1850±50° C., and the treatment time is 1.5 h, to obtain graphitized particles;
[0043] 90 parts of methyl vinyl silicone rubber, 10 parts of hydroxy silicone oil, 15 parts of graphite-like particles, 8 parts of white carbon black, 1.5 parts of triethylenediamine, 0.01 parts of platinum catalyst and 1 part of vulcanizing agent were mixed, and the mixture was homogenized by ultrasound to obtain silicone rubber slurry;
[0044] (3) Silicone rubber slurry is coated on both sides of the modified glass fiber cloth with a coating thickness of 150 μm. After coating, the surface of the fiber cloth is heated at 110±10°C for 3 min, and then the temperature is increased to 165±15°C for further heating for 5 min until the silicone rubber is completely cured to obtain an anti-aging fireproof cloth with a continuous morphology and a smooth surface.
[0045] Comparative Example 1
[0046] The fireproof cloth provided in this comparative example is prepared as follows:
[0047] (1) impregnating polyimide particles in propylene oxide with a concentration of 10 wt%, and then drying them in a nitrogen atmosphere at 200° C., mixing them with titanium dioxide particles at a mass ratio of 3:1 after drying, and placing the mixed particles in a vacuum carbonization furnace, and performing carbonization and graphitization heat treatment in succession under a nitrogen atmosphere, wherein the carbonization treatment temperature is 900±50° C., the treatment time is 1 h, and the graphitization treatment temperature is 1850±50° C., and the treatment time is 1.5 h, to obtain graphitized particles;
[0048] 90 parts of methyl vinyl silicone rubber, 10 parts of hydroxy silicone oil, 15 parts of graphite-like particles, 8 parts of white carbon black, 1.5 parts of triethylenediamine, 0.01 parts of platinum catalyst and 1 part of vulcanizing agent were mixed, and the mixture was homogenized by ultrasound to obtain silicone rubber slurry;
[0049] (2) Silicone rubber slurry is coated on both sides of the glass fiber cloth with a coating thickness of 150 μm. After coating, the surface of the fiber cloth is heated at 110±10°C for 3 min, and then the temperature is increased to 165±15°C for further heating for 5 min until the silicone rubber is completely cured to obtain a fireproof cloth. The morphology of the fireproof cloth is discontinuous, and there are some protrusions and pits on the surface.
[0050] Comparative Example 2
[0051] The fireproof cloth provided in this comparative example is prepared as follows:
[0052] (1) treating the glass fiber cloth with hydrochloric acid for 15 minutes and then soaking it in a carboxymethyl cellulose solution for 24 hours, scooping up the glass fiber cloth and subjecting it to continuous heating treatment, with the temperature in the first stage rising to 350±50°C and maintaining it for 1 hour, then rising to 1250±50°C and maintaining it for 1 hour, cooling it naturally and then washing it with ethanol and deionized water, and drying it at room temperature to obtain the modified glass fiber cloth;
[0053] (2) 90 parts of methyl vinyl silicone rubber, 10 parts of hydroxy silicone oil, 12 parts of titanium dioxide particles, 2 parts of antimony trioxide, 1.5 parts of anti-aging agent MMB, 8 parts of white carbon black, 1.5 parts of triethylenediamine, 0.01 parts of platinum catalyst, and 1 part of vulcanizing agent were mixed, and the mixture was homogenized by ultrasound to obtain silicone rubber slurry;
[0054] (3) Silicone rubber slurry is coated on both sides of the modified glass fiber cloth with a coating thickness of 150 μm. After coating, the surface of the fiber cloth is heated at 110±10°C for 3 min, and then the temperature is increased to 165±15°C for further heating for 5 min until the silicone rubber is completely cured to obtain fireproof cloth II. The morphology of fireproof cloth II is continuous, but there are some protrusions and pits on the surface.
[0055] Comparative Example 3
[0056] The fireproof cloth provided in this comparative example is prepared as follows:
[0057] (1) treating the glass fiber cloth with hydrochloric acid for 15 minutes and then soaking it in a carboxymethyl cellulose solution for 24 hours, scooping up the glass fiber cloth and subjecting it to continuous heating treatment, with the temperature in the first stage rising to 350±50°C and maintaining it for 1 hour, then rising to 1250±50°C and maintaining it for 1 hour, cooling it naturally and then washing it with ethanol and deionized water, and drying it at room temperature to obtain the modified glass fiber cloth;
[0058] (2) The polyimide particles are immersed in propylene oxide with a concentration of 10 wt %, and then dried in a nitrogen atmosphere at 200° C. The polyimide particles are placed in a vacuum carbonization furnace and subjected to carbonization and graphitization heat treatment in succession under a nitrogen atmosphere, wherein the carbonization treatment temperature is 900±50° C. and the treatment time is 1 h, and the graphitization treatment temperature is 1850±50° C. and the treatment time is 1.5 h, to obtain particle 1;
[0059] Mix 90 parts of methyl vinyl silicone rubber, 10 parts of hydroxy silicone oil, 20 parts of particles, 8 parts of white carbon black, 1.5 parts of triethylenediamine, 0.01 parts of platinum catalyst and 1 part of vulcanizing agent, and homogenize the mixture by ultrasonic wave to obtain silicone rubber slurry;
[0060] (3) Silicone rubber slurry is coated on both sides of the modified glass fiber cloth with a coating thickness of 150 μm. After coating, the surface of the fiber cloth is heated at 110±10°C for 3 min, and then the temperature is increased to 165±15°C for further heating for 5 min until the silicone rubber is completely cured to obtain fireproof cloth No. 3. The morphology of fireproof cloth No. 3 is continuous and the surface is smooth.
[0061] Comparative Example 4
[0062] The fireproof cloth provided in this comparative example is prepared as follows:
[0063] (1) treating the glass fiber cloth with hydrochloric acid for 15 minutes and then soaking it in a carboxymethyl cellulose solution for 24 hours, scooping up the glass fiber cloth and subjecting it to continuous heating treatment, with the temperature in the first stage rising to 350±50°C and maintaining it for 1 hour, then rising to 1250±50°C and maintaining it for 1 hour, cooling it naturally and then washing it with ethanol and deionized water, and drying it at room temperature to obtain the modified glass fiber cloth;
[0064] (2) placing the titanium dioxide particles into a vacuum carbonization furnace, and performing carbonization and graphitization heat treatments in succession under a nitrogen atmosphere, wherein the carbonization treatment temperature is 900±50°C, the treatment time is 1 h, and the graphitization treatment temperature is 1850±50°C, the treatment time is 1.5 h, to obtain particle 2;
[0065] 90 parts of methyl vinyl silicone rubber, 10 parts of hydroxy silicone oil, 20 parts of particle II, 8 parts of self-carbon black, 1.5 parts of triethylenediamine, 0.01 parts of platinum catalyst and 1 part of vulcanizing agent were mixed, and then the mixture was homogenized by ultrasonic wave to obtain silicone rubber slurry;
[0066] (3) Silicone rubber slurry is coated on both sides of the modified glass fiber cloth with a coating thickness of 150 μm. After coating, the surface of the fiber cloth is heated at 110±10°C for 3 min, and then the temperature is increased to 165±15°C for further heating for 5 min until the silicone rubber is completely cured to obtain fireproof cloth No. 4. The morphology of the fireproof cloth No. 4 is continuous and the surface is smooth.
[0067] Comparative Example 5
[0068] The fireproof cloth provided in this comparative example is prepared as follows:
[0069] (1) treating the glass fiber cloth with hydrochloric acid for 15 minutes and then soaking it in a carboxymethyl cellulose solution for 24 hours, scooping up the glass fiber cloth and subjecting it to continuous heating treatment, with the temperature in the first stage rising to 350±50°C and maintaining it for 1 hour, then rising to 1250±50°C and maintaining it for 1 hour, cooling it naturally and then washing it with ethanol and deionized water, and drying it at room temperature to obtain the modified glass fiber cloth;
[0070] (2) mixing polyimide particles and titanium dioxide particles in a mass ratio of 3:1, and using the mixed particles as particle three;
[0071] Mix 90 parts of methyl vinyl silicone rubber, 10 parts of hydroxy silicone oil, 15 parts of granular tris, 8 parts of white carbon black, 1.5 parts of triethylenediamine, 0.01 parts of platinum catalyst and 1 part of vulcanizing agent, and homogenize the mixture by ultrasonic wave to obtain silicone rubber slurry;
[0072] (3) Silicone rubber slurry is coated on both sides of the modified glass fiber cloth with a coating thickness of 150 μm. After coating, the surface of the fiber cloth is heated at 110±10°C for 3 min, and then the temperature is increased to 165±15°C for further heating for 5 min until the silicone rubber is completely cured to obtain fireproof cloth No. 5. The morphology of fireproof cloth No. 5 is continuous and the surface is smooth.
[0073] Comparative Example 6
[0074] The fireproof cloth provided in this comparative example is prepared as follows:
[0075] (1) treating the glass fiber cloth with hydrochloric acid for 15 minutes and then soaking it in a carboxymethyl cellulose solution for 24 hours, scooping up the glass fiber cloth and subjecting it to continuous heating treatment, with the temperature in the first stage rising to 350±50°C and maintaining it for 1 hour, then rising to 1250±50°C and maintaining it for 1 hour, cooling it naturally and then washing it with ethanol and deionized water, and drying it at room temperature to obtain the modified glass fiber cloth;
[0076] (2) The polyimide particles are immersed in propylene oxide with a concentration of 10 wt%, and then dried in a nitrogen atmosphere at 200° C. After drying, the particles are mixed with titanium dioxide particles at a mass ratio of 3:1, and the mixed particles are put into a vacuum carbonization furnace, and successively subjected to carbonization and graphitization heat treatment in a nitrogen atmosphere, wherein the carbonization treatment temperature is 900±50° C., the treatment time is 1 h, and the graphitization treatment temperature is 1850±50° C., and the treatment time is 1.5 h, to obtain graphitized particles;
[0077] 90 parts of methyl vinyl silicone rubber, 10 parts of hydroxy silicone oil, 20 parts of graphite-like particles, 8 parts of white carbon black, 1.5 parts of anti-aging agent MMB, 0.01 parts of platinum catalyst, and 1 part of vulcanizing agent were mixed, and then the mixture was homogenized by ultrasonic wave to obtain silicone rubber slurry;
[0078] (3) Silicone rubber slurry is coated on both sides of the modified glass fiber cloth with a coating thickness of 150 μm. After coating, the surface of the fiber cloth is heated at 110±10°C for 3 min, and then the temperature is increased to 165±15°C for further heating for 5 min until the silicone rubber is completely cured to obtain fireproof cloth No. 6. The morphology of the fireproof cloth No. 6 is continuous and the surface is smooth.
[0079] 3. Test Verification
[0080] The fireproof cloths prepared in Examples 1-2 and Comparative Examples 1-6 were used as test samples to conduct the following tests:
[0081] (1) Tensile strength: The tensile strength of each test sample was measured using a tensile testing machine. The test method was based on the standard GB / T528-2009.
[0082] (2) Flame retardancy: The flame retardancy test method refers to the standard UL94-2009; each test sample is heated to 1000°C at a rate of 10°C / min, maintained for 1 hour, and the ablation mass change rate is measured;
[0083] (3) Aging resistance: After placing each test sample in a LX-8847 UV aging box for 48 hours, take it out and use (1) and (2) to measure its tensile strength and flame retardancy.
[0084] The above tests were conducted multiple times, and the test results were averaged.
[0085] The test results are recorded in the following table:
[0086]
[0087] Note: ① is the test result of each test sample before aging, ② is the test result of each test sample after aging.
[0088] It can be seen from Examples 1-2 and Comparative Examples 1-6 that the present invention improves the tensile strength of the glass fiber cloth by treating the glass fiber cloth, and increases the compatibility of the glass fiber cloth with the silicone rubber slurry, so that it can be better combined with methyl vinyl silicone rubber. The use of polyimide particles instead of antimony trioxide as a flame retardant component and titanium dioxide as an anti-aging component mainly utilizes its shielding properties as a physical anti-aging means, and by subjecting the polyimide particles and titanium dioxide particles to high-temperature treatment, the flame retardancy of the polyimide is enhanced, and the titanium dioxide can be promoted to transform into a rutile type, further enhancing its stability. The present invention also utilizes triethylenediamine to react with free radicals in the silicone rubber slurry to further achieve an anti-aging effect.
[0089] By comparing the test results of Example 2 and Comparative Example 1, it is found that the modified glass fiber cloth obtained after treating the glass fiber cloth can enhance the tensile strength of the product. It is speculated that the acid treatment increases the silica content of the glass fiber cloth, and the high temperature treatment further enhances its strength. However, the modified glass fiber cloth has little effect on the flame retardancy and aging resistance of the product.
[0090] By comparing the test results of Example 2 and Comparative Examples 2-5, it is found that the use of the graphite-like particles of the present invention as both a flame retardant component and an anti-aging component is better than the use of antimony trioxide and the anti-aging agent MMB, and also avoids the situation where antimony trioxide is easily oxidized with silica gel, resulting in poor aging resistance of the product; at the same time, the present invention performs high-temperature treatment on the polyimide particles and titanium dioxide particles, and increases their compatibility with silicone rubber to make their combination more stable. It can be seen from Example 2 and Comparative Example 5 that the flame retardant effect and anti-aging effect of the product are better.
[0091] By comparing the test results of Example 2 and Comparative Examples 2 and 6, it is found that in the presence of the anti-aging agent MMB, triethylenediamine does not produce a synergistic effect with it, so that the anti-aging performance of the product is improved. However, from the comparison between Example 2 and Comparative Example 6, triethylenediamine can significantly improve the anti-aging performance of the product, and triethylenediamine has a certain cross-linking effect, which can improve the hardness, wear resistance and corrosion resistance of the product.
[0092] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. A method for preparing an anti-aging fireproof cloth for building materials, characterized in that: The following steps are involved: The glass fiber cloth is treated with acid and then immersed in a carboxymethyl cellulose solution, and then the glass fiber cloth is continuously heated to obtain a modified glass fiber cloth; Methyl vinyl silicone rubber, hydroxy silicone oil, graphite-like particles, white carbon black, triethylenediamine, a platinum catalyst, and a vulcanizing agent are mixed and homogenized to obtain a silicone rubber slurry, wherein the graphite-like particles are obtained by heat-treating polyimide particles and titanium dioxide particles; Silicone rubber slurry is coated on both sides of the modified glass fiber cloth, and the surface of the fiber cloth is heated after coating until the silicone rubber is completely cured to obtain the anti-aging fireproof cloth.
2. The method for preparing an anti-aging fireproof cloth for building materials according to claim 1, characterized in that: The acid treatment is to treat in hydrochloric acid at a temperature of 80-90° C. and a concentration of 1.5-3.5 mol / L for 15-20 min; the concentration of the carboxymethyl cellulose solution is 7.0-10.0 wt %.
3. The method for preparing an anti-aging fireproof cloth for building materials according to claim 1, characterized in that: The continuous heating treatment is as follows: in the first stage, the temperature is raised to 300-400° C. and maintained for 0.5-1 h, then raised to 1200-1300° C. and maintained for 0.5-1 h, and then washed with ethanol and deionized water after natural cooling.
4. The method for preparing an anti-aging fireproof cloth for building materials according to claim 1, characterized in that: In parts by weight, the weight proportions of the components in the silicone rubber slurry are: 80-90 parts of methyl vinyl silicone rubber, 5-10 parts of hydroxy silicone oil, 10-20 parts of graphite-like particles, 6-10 parts of white carbon black, 1-3 parts of triethylenediamine, 0.01-0.05 parts of platinum catalyst, and 1-2 parts of vulcanizing agent.
5. The method for preparing an anti-aging fireproof cloth for building materials according to claim 1, characterized in that: The preparation process of the graphitized particles is as follows: The polyimide particles are immersed in propylene oxide with a concentration of 10-12wt%, and then dried in a nitrogen atmosphere at 200-300°C. After drying, they are mixed with titanium dioxide particles, and the mixed particles are successively subjected to carbonization and graphitization heat treatment in a nitrogen atmosphere to obtain graphitized particles.
6. The method for preparing an anti-aging fireproof cloth for building materials according to claim 5, characterized in that: The carbonization treatment temperature is 800-1000° C. and the treatment time is 1-2 hours. The graphitization treatment temperature is 1700-2000° C. and the treatment time is 1-2 hours.
7. The method for preparing an anti-aging fireproof cloth for building materials according to claim 5, characterized in that: The mass ratio of the polyimide particles to the titanium dioxide particles is 3:
1.
8. The method for preparing an anti-aging fireproof cloth for building materials according to claim 1, characterized in that: The vulcanizing agent is one of dipentadienyl and tert-butyl perbenzoate.
9. The method for preparing an anti-aging fireproof cloth for building materials according to claim 1, characterized in that: The fiber cloth surface is subjected to heating treatment after coating as follows: firstly, the surface is heated at 100-120° C. for 2-5 minutes, then the temperature is raised to 150-180° C. and the heating is continued for 5-10 minutes until the silicone rubber is completely cured. 10.An anti-aging fireproof cloth for building materials, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Cited By
Fireproof material based on liquid silica gel and glass fiber and preparation method thereof
CN120924040A
